2023
DOI: 10.32479/ijeep.13612
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Consumer Attitude and Renewable Energy towards Environmental Friendly Policies in the Intention to Comply With the Paid Plastic Environmental Friendly Policy

Abstract: The purpose of this study is to determine the effect of consumer attitudes and renewable energy on the intention to comply with the paid plastic environmentally friendly policy in North Sumatra Province through the environmental friendly policy variable made by the Government as a moderator variable.In this study the variables used are exogenous variables, namely consumer attitudes and renewable energy, while the endogenous variables areintention to comply with the paid plastic eco-friendly policy in North Sum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 28 publications
(33 reference statements)
0
7
0
Order By: Relevance
“…Renewable energy sources, such as solar, wind, hydro, geothermal, and biomass, can be harnessed naturally and indefinitely, ensuring a continuous supply (Singh et al, 2020). When comparing conventional energy, which is obtained from fossil fuels, to renewable energy, it is commonly concluded that renewable energy has a lower environmental impact (Sinaga and Sitorus, 2023). Employing renewable energy sources can effectively mitigate environmental contaminants and greenhouse gas emissions (Syed Shaharuddin et al, 2021).…”
Section: Renewable Energymentioning
confidence: 99%
See 1 more Smart Citation
“…Renewable energy sources, such as solar, wind, hydro, geothermal, and biomass, can be harnessed naturally and indefinitely, ensuring a continuous supply (Singh et al, 2020). When comparing conventional energy, which is obtained from fossil fuels, to renewable energy, it is commonly concluded that renewable energy has a lower environmental impact (Sinaga and Sitorus, 2023). Employing renewable energy sources can effectively mitigate environmental contaminants and greenhouse gas emissions (Syed Shaharuddin et al, 2021).…”
Section: Renewable Energymentioning
confidence: 99%
“…Employing renewable energy sources can effectively mitigate environmental contaminants and greenhouse gas emissions (Syed Shaharuddin et al, 2021). Presented below are few illustrations of contemporary alternative energy sources: Solar Energy (Solar Power), wherein the sun supplies solar energy that can then be harnessed by solar panels to produce electricity (Agustina et al, 2023;Napitupulu et al, 2023). Solar power systems can be utilized for power generation in both commercial and residential settings.…”
Section: Renewable Energymentioning
confidence: 99%
“…The shift to renewable energy requires the implementation of policies and procedures that facilitate the use of more environmentally friendly energy sources and reduce the impact of climate change (Maulidia et al, 2019). (Napitupulu et al, 2023;Sinaga and Sitorus, 2023) Some of the main components of the Renewable Energy Transition are as follows: 1. Utilization of renewable resources, where recyclable natural resources such as solar, wind, water, geothermal, and biomass are renewable energy sources.…”
Section: Renewable Energy Transitionmentioning
confidence: 99%
“…This includes methods that help conserve water and land and reduce the environmental impact of renewable energy initiatives (Kumar and Ghosh, 2017). (Sinaga and Sitorus, 2023) Indicators of the renewable energy transition undertaken by stakeholders include:…”
Section: Energy Efficiency Where the Transition To Renewable Energymentioning
confidence: 99%
“…One of the efforts that can be made is through the use of renewable energy in building houses (Maglad et al, 2023). Residential houses that are environmentally friendly and focus on renewable energy can provide long-term benefits for the environment as well as for consumers who choose to live in them (Sinaga and Sitorus, 2023;Yunus et al, 2023). Renewable energy suitable for residential homes no longer uses fossil energy as a driver in electrical energy and of course a replacement energy is needed that comes from natural energy that will be used to drive electricity in the house (Hoang et al, 2021).…”
Section: Introductionmentioning
confidence: 99%